Playing for change: (semi-)professionalization, social policy, and power struggles in Argentine women's football. (18th August 2021) - Garton, Gabriela; Hijós, Nemesia; Alabarces, Pablo
ABSTRACT: The professionalization of the Argentine women's first division in 2019 allows an in-depth analysis of an underdeveloped and historically marginalized women's football in Latin America. Following Argentina's participation in the 2018 Women's Copa América in Chile and the 2019 FIFA Women's World Cup in France, the precarious conditions faced by the female football players were exposed as never before, drawing attention from major national and international news outlets. In those years, the players organized the first strike in a national team history; their actions were accompanied by the regional feminist movement, local organizations, increased media coverage, and new gender-equity policies imposed by the sport's international governing bodies. Then, the Argentine Football Association's (AFA) decided to professionalize women's football in the country. This article hopes to shed light on the struggles and progress of female participants in atraditionally androcentric sport practice and analyse the response from the institutions.